Near-infrared fluorescence imaging with indocyanine green-lactosomes in a mouse model of rheumatoid arthritis. Issue 6 (1st November 2016) - Onishi, Shinzo; Sakane, Masataka; Tsukanishi, Toshinori; Funayama, Toru; Ozeki, Eiichi; Hara, Isao; Yamazaki, Masashi
Abstract: Objectives : The early diagnosis and treatment of rheumatoid arthritis (RA) is important to reduce joint destruction. Many of the current imaging techniques have disadvantages, such as the need for contrast agents and interpretation by specialists. Fluorescence imaging is an emerging technique that overcomes some of these problems. The aim of this study was to determine whether near-infrared (NIR) fluorescence imaging of indocyanine green (ICG)-lactosomes can detect joint inflammation in a mouse model of RA. Methods : Control and arthritic SKG/Jcl mice were injected with ICG alone or ICG-lactosomes and examined by NIR fluorescence imaging. Arthritis severity was assessed macroscopically and histopathologically. Results : ICG fluorescence was detected in the liver soon after injection and then decreased over the next several hours. ICG was not detected in the joints of control or arthritic mice. In contrast, ICG-lactosomes remained in mice for at least 48 h and accumulated specifically at inflamed joints. ICG-lactosome fluorescence was higher in arthritic versus normal joints at all times examined and was maximal at 24 h after injection. Conclusions : NIR fluorescence imaging of ICG-lactosomes detects arthritic joints in a mouse model of RA. ICG-lactosomes may preferentially localize to inflamed joints via enhanced permeability and retention.